KONSEP KAFAAH DALAM PERNIKAHAN PERSPEKTIF ULAMA DI KECAMATAN KANDANGAN - Erma, Erma Sauva Asvia (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Abstract This research discusses the concept of kafaah in marriage from the Ulama in Kandangan District. This research aims to determine the concept of the perspective of Ulama in Kandangan District. This reseacrh is field are Ulama who live in Kandangan District, and are registered or regestered with the MUI (Indonesian Ulama Council), and the object of the research is the Concept of Kafaah in Marriage from the Ulama Perspective in Kandangan District. The data analysis technique in this researcrh uses qualitative methods, and the results obtained from this research are that the Ulama agree that it is mandatory to apply the concept of Kafaah in marriage which emphasizes aspects of religios issues. Keywords: Kafaah, Ulama